Investasi Asing Langsung dan Pertumbuhan Ekonomi: Perbandingan Empiris Indonesia dan Singapura - Eko Atmayudi Gandhi; Esti Pasaribu; Retno Agustina Ekaputri; Ratu Eva Febriani (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2022)
This study assesses the causal relationship to see whether the investment will affect economic growth. The data was taken from 1970-2020 in unit percentages, so the results obtained will lead to the research objectives. This research is also the direction of the relationship between two variables using several tests, namely the Granger Casualty and Error Correction Model (ECM). The results show a one-way causal relationship between FDI and economic growth and determine the lag that has been tested. The optimal lag in the second year of FDI is proven to affect economic growth in Indonesia in two years. There is a long-term and short-term relationship when direct investment affects Singapore's economic growth in the period 1970-2020. As a developed country, the creation of a one-way causal relationship, foreign direct investment is proven to affect economic growth. Thus, compared to developing countries such as Indonesia, where the optimal lag test is carried out, the one-way relationship of foreign investment is proven to affect Singapore's economic growth within two years, including the long term. And the short-term relationship when direct investment involves economic growth.